1996
DOI: 10.2527/1996.7471530x
|View full text |Cite
|
Sign up to set email alerts
|

Cultured porcine myogenic cells produce insulin-like growth factor binding protein-3 (IGFBP-3) and transforming growth factor beta-1 stimulates IGFBP-3 production.

Abstract: Insulin-like growth factor binding proteins (IGFBP) may act locally as autocrine or paracrine regulators of insulin-like growth factor activity in specific tissues such as muscle. Although secretion of IGFBP by cultured myogenic cell lines has been examined, little is known about secretion of IGFBP by primary myogenic cell cultures. This may be because primary myogenic cultures contain non-muscle cells (fibroblasts) that complicate interpretation of IGFBP determinations. We have circumvented this problem by su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 40 publications
2
40
0
Order By: Relevance
“…Although it has been reported that IGFBP-3 is GH and IGF-I dependent (Spagnoli & Rosenfeld 1997), acute LPS administration, in a higher dose than in the present study (1 mg/kg), increases hepatic IGFBP-3 levels together with a significant decrease in serum GH and IGF-I levels (Fan et al 1994). These results suggest that other factors may modulate the serum concentration of IGFBP-3, and are in accordance with other data previously reported showing that IL-1, TNF and transforming growth factor (TGF-) induce IGFBP-3 synthesis (Olney et al 1995, Hembree et al 1996, Han et al 1997. Since LPS administration has been shown to increase not only IL-1 and TNF but also hepatic TGF mRNA levels (Masuhara 1995), these can be possible mechanisms by which LPS increases circulating IGFBP-3.…”
Section: Discussionsupporting
confidence: 82%
“…Although it has been reported that IGFBP-3 is GH and IGF-I dependent (Spagnoli & Rosenfeld 1997), acute LPS administration, in a higher dose than in the present study (1 mg/kg), increases hepatic IGFBP-3 levels together with a significant decrease in serum GH and IGF-I levels (Fan et al 1994). These results suggest that other factors may modulate the serum concentration of IGFBP-3, and are in accordance with other data previously reported showing that IL-1, TNF and transforming growth factor (TGF-) induce IGFBP-3 synthesis (Olney et al 1995, Hembree et al 1996, Han et al 1997. Since LPS administration has been shown to increase not only IL-1 and TNF but also hepatic TGF mRNA levels (Masuhara 1995), these can be possible mechanisms by which LPS increases circulating IGFBP-3.…”
Section: Discussionsupporting
confidence: 82%
“…Cultured PEMCs produce IGFBP-3, and levels of IGFBP-3 mRNA and protein decrease significantly during differentiation and then increase after differentiation is complete (Hembree et al 1996, Yang et al 1999. These changes in IGFBP-3 mRNA concentration during differentiation suggest that IGFBP-3 may play a role in myogenesis and/or alterations in proliferation of cultured PEMCs during differentiation.…”
Section: Introductionmentioning
confidence: 86%
“…Binding proteins were detected with 125 I-IGF-I as described previously (Hembree et al 1996, Yang et al 1999.…”
Section: Ligand Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultured skeletal myoblasts do not appear to have abundant cell-associated IGFBPs, but secrete either a single IGFBP or a wide variety of combinations of soluble IGFBPs including IGFBP-2, -3, -4, -5, -6 and -7 (rp1) (McCusker et al 1989b, Ernst et al 1992, James et al 1993, McFarland et al 1993, Kou et al 1994, McCusker & Clemmons 1994, 1998, Bach et al 1995, Ernst & White 1996, Hembree et al 1996, Damon et al 1997, Ewton et al 1998, Musaro & Rosenthal 1999, Yang et al 1999, Bayol et al 2000, Crown et al 2000, Haugk et al 2000, Meadows et al 2000, Foulstone et al 2001, Rousse et al 2001, Yi et al 2001. With such an array of IGFBP profiles, it is difficult to interpret the specific role of a given IGFBP to myoblast function although clearly IGFBPs can act as autocrine and paracrine growth and differentiation modulators (McCusker & Clemmons 1988, Hodgkinson et al 1989, Tollefsen et al 1989, Bach et al 1994, Ewton & Florini 1995, Rotwein et al 1995, Silverman et al 1995, Ernst et al 1996, Ernst & White 1996, James et al 1996, Stewart et al 1996, Damon et al 1998a,b, Fligger et al 1998, Rousse et al 1998, Meadows et al 2000, Foulstone et al 2001…”
Section: Introductionmentioning
confidence: 99%